Large-scale analysis of putative plasmids in clinical multidrug-resistant Escherichia coli isolates from Vietnamese patients - Nguyen, Quang Huy; Le, Thi Thu Hang; Nguyen, Son Thai; Nguyen, Kieu-Oanh Thi; Quyen, Dong Van; Hayer, Juliette; Bañuls, Anne-Laure; Tran, Tam Thi Thanh (Frontiers in Microbiology, 2023)
In the past decades, extended-spectrum beta-lactamase (ESBL)-producing and carbapenem-resistant (CR) Escherichia coli isolates have been detected in Vietnamese hospitals. The transfer of antimicrobial resistance (AMR) genes carried on plasmids is mainly responsible for the emergence of multidrug-resistant E. coli strains and the spread of AMR genes through horizontal gene transfer. Therefore, it is important to thoroughly study the characteristics of AMR gene-harboring plasmids in clinical multidrug-resistant bacterial isolates. To this aim, the profiles of plasmid assemblies were determined by analyzing previously published whole-genome sequencing data of 751 multidrug-resistant E. coli isolates from Vietnamese hospitals in order to identify the risk of AMR gene horizontal transfer and dissemination. The number of putative plasmids in isolates was independent of the sequencing coverage. These putative plasmids originated from various bacterial species, but mostly from the Escherichia genus, particularly E. coli species. Many different AMR genes were detected in plasmid contigs of the studied isolates, and their number was higher in CR isolates than in ESBL-producing isolates. Similarly, the blaKPC-2, blaNDM-5, blaOXA-1, blaOXA-48, and blaOXA-181 β-lactamase genes, associated with resistance to carbapenems, were more frequent in CR strains. Sequence similarity network and genome annotation analyses revealed high conservation of the β-lactamase gene clusters in plasmid contigs that carried the same AMR genes. Our study provides evidence of horizontal gene transfer in multidrug-resistant E. coli isolates via conjugative plasmids, thus rapidly accelerating the emergence of resistant bacteria. Besides reducing antibiotic misuse, prevention of plasmid transmission also is essential to limit antibiotic resistance.